Theoretical simulation and analysis of large size BMP-LSC by 3D Monte Carlo ray tracing model - 张峰 张宁宁 张义 闫森 孙松 鲍骏 高琛 (Chinese physics B, 2017)
Luminescent solar concentrators（LSC） can reduce the area of solar cells by collecting light from a large area and concentrating the captured light onto relatively small area photovoltaic（PV） cells, and thereby reducing the cost of PV electricity generation. LSCs with bottom-facing cells（BMP-LSC） can collect both direct light and indirect light, so further improving the efficiency of the PV cells. However, it is hard to analyze the effect of each parameter by experiment because there are too many parameters involved in the BMP-LSC. In this paper, all the physical processes of the light transmission and collection in the BMP-LSC were analyzed. A three-dimensional Monte Carlo ray tracing program was developed to study the transmission of photons in the LSC. A larger-size LSC was simulated, and the effects of dye concentration, the LSC thickness, the cell area, and the cell distance were systematically analyzed.